The inducible caspase-9 suicide gene system as a “safety switch” to limit on-target, off-tumor toxicities of chimeric antigen receptor T cells - Gargett, Tessa; Brown, Michael P. (Frontiers in Pharmacology, 2014)
Immune modulation has become a central element in many cancer treatments, and T cells genetically engineered to express chimeric antigen receptors (CAR) may provide a new approach to cancer immunotherapy. Autologous CAR T cells that have been re-directed towards tumor-associated antigens (TAA) have shown promising results in phase 1 clinical trials, with some patients undergoing complete tumor regression. However this T-cell therapy must carefully balance effective T-cell activation, to ensure antitumor activity, with the potential for uncontrolled activation that may produce immunopathology. An inducible Caspase 9 (iCasp9) ‘safety switch’ offers a solution that allows for the removal of inappropriately activated CAR T cells. The induction of iCasp9 depends on the administration of the small molecule dimerizer drug AP1903 and dimerization results in rapid induction of apoptosis in transduced cells, preferentially killing activated cells expressing high levels of transgene. The iCasp9 gene has been incorporated into vectors for use in preclinical studies and demonstrates effective and reliable suicide gene activity in phase 1 clinical trials. A third-generation CAR incorporating iCasp9 re-directs T cells towards the GD2 TAA. GD2 is over-expressed in melanoma and other malignancies of neural crest origin and the safety and activity of these GD2-iCAR T cells will be investigated in CARPETS and other actively recruiting phase 1 trials.